2012
DOI: 10.5194/npg-19-577-2012
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis of ULF electromagnetic emissions in possible association with earthquakes in China

Abstract: Abstract. The long-term data (during the period of 1 March 2003 through 31 December 2006) of ULF geomagnetic variations observed at Kashi station (geographic coordinates: 39.5 • N, 76.0 • E) in China have been used to investigate the long-term variation of fractal dimension of ULF emissions. We have studied the changes in fractal dimension in association with several earthquakes around the observation station. It is then found that a significant change (or decrease) in the fractal dimension of the Z component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 40 publications
2
23
1
Order By: Relevance
“…Up to now no strong evidence has been provided to reject the findings of these reviews. Ida et al (2012) criticized the findings of some of these papers, such as, Campbell (2009) and Thomas et al (2009a, b), but they did not provide any solid evidence in support of their weak criticism. Among these reviews, there are the studies by Masci (2010Masci ( , 2013, which demonstrated that the fractal analysis of the geomagnetic field in the ULF band is not a good indicator of an imminent earthquake.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Up to now no strong evidence has been provided to reject the findings of these reviews. Ida et al (2012) criticized the findings of some of these papers, such as, Campbell (2009) and Thomas et al (2009a, b), but they did not provide any solid evidence in support of their weak criticism. Among these reviews, there are the studies by Masci (2010Masci ( , 2013, which demonstrated that the fractal analysis of the geomagnetic field in the ULF band is not a good indicator of an imminent earthquake.…”
Section: Discussionmentioning
confidence: 96%
“…These papers reported a relation between the fractal dimension variations and the occurrence of strong earthquakes such as the 1993 Guam earthquake, the 1996 Biak earthquake, and the 2000 Izu earthquake swarm. Ida et al (2012) failed to address the review by Masci (2010) that demonstrated that the fractal precursors documented in these papers are signals that are part of normal geomagnetic activity, which therefore cannot be described as earthquakerelated anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations